Thymic stromal lymphopoietin and interleukin‐4 mediate the pathogenesis of halothane‐induced liver injury in mice. Issue 5 (20th May 2014) - Proctor, William R.; Chakraborty, Mala; Fullerton, Aaron M.; Korrapati, Midhun C.; Ryan, Pauline M.; Semple, Kenrick; Morrison, Jeffrey C.; Berkson, Julia D.; Chea, Lynette S.; Yang, Qian; Li, Albert P.; Spolski, Rosanne; et al.
<x xml:space="preserve">Abstract</x> Liver eosinophilia has been associated with incidences of drug‐induced liver injury (DILI) for more than 50 years, although its role in this disease has remained largely unknown. In this regard, it was recently shown that eosinophils played a pathogenic role in a mouse model of halothane‐induced liver injury (HILI). However, the signaling events that drove hepatic expression of eosinophil‐associated chemokines, eotaxins, eosinophil infiltration, and subsequent HILI were unclear. We now provide evidence implicating hepatic epithelial‐derived cytokine thymic stromal lymphopoietin (TSLP) and type 2 immunity, in particular, interleukin‐4 (IL‐4) production, in mediating hepatic eosinophilia and injury during HILI. TSLP was constitutively expressed by mouse hepatocytes and increased during HILI. Moreover, the severity of HILI was reduced in mice deficient in either the TSLP receptor (TSLPR) or IL‐4 and was accompanied by decreases in serum levels of eotaxins and hepatic eosinophilia. Similarly, concanavalin A–induced liver injury, where type 2 cytokines and eosinophils play a significant role in its pathogenesis, was also reduced in TSLPR‐deficient mice. Studies in vitro revealed that mouse and human hepatocytes produce TSLP and eotaxins in response to treatment with combinations of IL‐4 and proinflammatory cytokines IL‐1β and tumor necrosis factor alpha. Conclusion: This report provides the first evidence implicating roles for hepatic TSLP signaling, type 2 immunity, and eosinophilia in mediating liver injury caused by a drug. (Hepatology 2014;60:1741‐1752)